Penyuluhan pentingnya pelestarian ekosistem Danau Timbang Bunga Pengantin di Desa Sungai Sorik Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi - Yusni Ikhwan Siregar; Syafruddin Nasution (PELANTAR PRESS, 2021)
Oxbow lake ecosystem have been used by local people traditionally along with the human history. The ecosystem were of important for clean water resources, fishing and cage culture, collecting aquatic fauna as well as rice field. However, more intense human intervention has brought about recently an effect on the sustainability of the ecosystem in term of ecological, social economical perspective. Danau Timbang Bunga Pengantin of Sungai Sorik, were developed for tourist destination especially for water attraction activities, floating restaurant, and fish cage culture. As such, the ecological burden stressors increased significantly. The present study aimed at promoting awareness and participation of local people on conservation and protection of the ecosystem from unsustainable uses, by attending group extension in classroom and observation outdoor. The results showed that 60% of the community were just aware of the effect of certain activities done to the sustainability of the lake. Responses of the participants in the classroom categorized high and curious to participate on the conservation of the lake.